Optically anisotropic laminate, method of manufacturing the same, circularly polarizing plate, and image display device

By using an optical opposite-sex layer composed of multiple optical opposite-sex layers in a high temperature environment, combined with a liquid crystal alignment layer, the problem of insufficient thermal stability and chromatic aberration ability of optical opposite-sex layers in the prior art in the high temperature environment is solved, and excellent thermal stability and chromatic aberration suppression effect are achieved.

JP2025039589AActive Publication Date: 2025-03-21ZEON CORP
View PDF 17 Cites 0 Cited by

Patent Information

Application Number
JP2024227843
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-02-28
Filing Date
2024-12-24
Publication Date
2025-03-21
Estimated Expiration
2043-01-24

AI Technical Summary

Technical Problem

The prior art is difficult to provide an optical opposite-sex layer laminate in a high-temperature environment that can effectively suppress color changes caused by external light reflection and has excellent thermal stability.

Method used

An optical opposite-sex layer consisting of the first, second and third optical opposite-sex layers is used, wherein the optical characteristics of each layer satisfy a specific equation relationship, and through a specific layer sequence and optical axis angle arrangement, combined with a liquid crystal alignment layer, an optical opposite-sex layer with excellent thermal stability and chromatic difference suppression ability is formed.

Benefits of technology

It realizes that while maintaining the stability of optical performance in a high-temperature environment, it effectively suppresses color changes caused by external light reflection, and improves the thermal stability and application performance of the optical opposite-sex layer laminate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025039589000001_ABST
    Figure 2025039589000001_ABST
Patent Text Reader

Abstract

To provide an optically anisotropic laminate which can be used to produce a circularly polarizing plate capable of preventing coloring caused by external light reflection both in a direction normal to a display surface and oblique directions, and which offers superior heat resistance.SOLUTION: An optically anisotropic laminate disclosed herein comprises a first optically anisotropic layer, a second optically anisotropic layer, and a third optically anisotropic layer and satisfies the following expressions (1), (2), (3), (4), and (5): nx1>ny1≥nz1 ...(1), nz2≥nx2>ny2 ...(2), nz3>nx3≥ny3 ...(3), Re1(450) / Re1(550)<Re2(450) / Re2(550) ...(4), Re1(550)>Re2(550)>Re3(550) ...(5). An angle between a slow axis of the first optically anisotropic layer and a slow axis of the second optically anisotropic layer is in a range of 85° to 95°, inclusive, and Re1(550) is 220 nm or greater.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an optically anisotropic laminate and a method for producing the same, as well as a circularly polarizing plate and an image display device. [Background technology]

[0002] Image display devices such as organic electroluminescence image display devices (hereinafter, occasionally referred to as "organic EL image display devices") and liquid crystal image display devices may be provided with an optically anisotropic laminate in which multiple layers having optical anisotropy are stacked (see Patent Documents 1 and 2). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2015-210459 A (Corresponding Foreign Publication: U.S. Patent Application Publication No. 2017 / 052300 Specification) [Patent Document 2] JP 2014-026266 A (Corresponding Foreign Publication: U.S. Patent Application Publication No. 2015 / 168624) Summary of the Invention [Problem to be solved by the invention]

[0004] Image display devices are sometimes used in high-temperature environments, and therefore it is preferable that the optically anisotropic laminate incorporated in the image display device has heat resistance and exhibits small retardation fluctuation due to heat. However, the techniques of Patent Documents 1 and 2 can provide a circular polarizing plate that can suppress coloring due to reflection of external light in both the front direction and the inclined direction of the display surface by combining it with a linear polarizer, and it was sometimes difficult to obtain an optically anisotropic laminate with excellent heat resistance.

[0005] Therefore, there is a demand for an optically anisotropic laminate that can provide a circular polarizing plate capable of suppressing coloring due to reflection of external light in both the front direction and the inclined direction of the display surface and that has excellent heat resistance. [Means for solving the problem]

[0006] The present inventors have conducted extensive research to solve the above problems, and as a result, have found that the above problems can be solved by an optically anisotropic laminate including a first optically anisotropic layer, a second optically anisotropic layer, and a third optically anisotropic layer, each of which has specific optical properties, and have thus completed the present invention. That is, the present invention provides the following.

[0007] [1] An optically anisotropic laminate comprising a first optically anisotropic layer, a second optically anisotropic layer, and a third optically anisotropic layer, satisfying the following formulas (1), (2), (3), (4), and (5), and an angle between a slow axis of the first optically anisotropic layer and a slow axis of the second optically anisotropic layer is 85° or more and 95° or less. nx1>ny1≧nz1 (1) nz2≧nx2>ny2 (2) nz3>nx3≧ny3 (3) Re1(450) / Re1(550) <Re2(450) / Re2(550) (4) Re1(550)>Re2(550)>Re3(550) (5) however, nx1 represents a refractive index in an in-plane direction of the first optically anisotropic layer that gives the maximum refractive index, ny1 represents a refractive index in an in-plane direction of the first optically anisotropic layer that is perpendicular to the direction that gives nx1, and nz1 represents a refractive index in a thickness direction of the first optically anisotropic layer, nx2 represents a refractive index in an in-plane direction of the second optically anisotropic layer that gives the maximum refractive index, ny2 represents a refractive index in an in-plane direction of the second optically anisotropic layer that is perpendicular to the direction that gives nx2, and nz2 represents a refractive index in a thickness direction of the second optically anisotropic layer, nx3 represents a refractive index in an in-plane direction of the third optically anisotropic layer that gives the maximum refractive index, ny3 represents a refractive index in an in-plane direction of the third optically anisotropic layer that is perpendicular to the direction that gives nx3, and nz3 represents a refractive index in a thickness direction of the third optically anisotropic layer, Re1(450) represents an in-plane retardation of the first optically anisotropic layer at a wavelength of 450 nm, and Re1(550) represents an in-plane retardation of the first optically anisotropic layer at a wavelength of 550 nm, Re2(450) represents an in-plane retardation of the second optically anisotropic layer at a wavelength of 450 nm, and Re2(550) represents an in-plane retardation of the second optically anisotropic layer at a wavelength of 550 nm, Re3(550) represents the in-plane retardation of the third optically anisotropic layer at a wavelength of 550 nm. [2] The optically anisotropic laminate according to [1], further satisfying the following formula (6): 100nm≦(Re1(550)-Re2(550))≦180nm (6) Here, Re1(550) and Re2(550) are each as defined above. [3] The optically anisotropic laminate according to [1] or [2], further satisfying the following formula (7): Re2(450) / Re2(550)-Re1(450) / Re1(550)≧0.05 (7) Here, Re1(450), Re1(550), Re2(450), and Re2(550) are each as defined above. [4] The first optically anisotropic layer is a first stretched layer obtained by stretching a first resin layer, The optically anisotropic laminate according to any one of [1] to [3], wherein the first resin layer contains a resin (A) having a positive intrinsic birefringence value. [5] The optically anisotropic laminate according to any one of [1] to [3], wherein the first optically anisotropic layer comprises a liquid crystal alignment layer. [6] The second optically anisotropic layer is a second stretched layer obtained by stretching a second resin layer, The optically anisotropic laminate according to any one of [1] to [5], wherein the second resin layer contains a resin (B) having a negative intrinsic birefringence value. [7] The optically anisotropic laminate according to any one of [1] to [5], wherein the second optically anisotropic layer comprises a liquid crystal alignment layer. [8] The optically anisotropic laminate according to any one of [1] to [7], wherein the third optically anisotropic layer comprises a liquid crystal alignment layer. [9] The third optically anisotropic layer is a third stretched layer obtained by stretching a third resin layer, The optically anisotropic laminate according to any one of [1] to [7], wherein the third resin layer contains a resin (C) having a negative intrinsic birefringence value.

[10] The first optically anisotropic layer, the second optically anisotropic layer, and the third optically anisotropic layer in this order, or the first optically anisotropic layer, the third optically anisotropic layer, and the second optically anisotropic layer in this order, or The optically anisotropic laminate according to any one of [1] to [9], comprising the third optically anisotropic layer, the first optically anisotropic layer, and the second optically anisotropic layer in this order.

[11] A linear polarizer; A circularly polarizing plate comprising the optically anisotropic laminate according to any one of [1] to

[10] .

[12] The circularly polarizing plate according to

[11] , wherein the angle between the absorption axis of the linear polarizer or the transmission axis of the linear polarizer and the slow axis of the first optically anisotropic layer is 40° or more and 50° or less.

[13] An image display device comprising the circularly polarizing plate according to

[11] or

[12] and an organic electroluminescence element, An image display device comprising the linear polarizer, the optically anisotropic laminate, and the organic electroluminescence element in this order.

[14] A method for producing an optically anisotropic laminate, comprising the steps of: The optically anisotropic laminate is the optically anisotropic laminate according to [4], wherein the second optically anisotropic layer is a second stretched layer obtained by stretching a second resin layer, and the second resin layer contains a resin (B) having a negative intrinsic birefringence value; The manufacturing method comprises: A step (1a) of applying a coating liquid (B) containing the resin (B) onto the first resin layer to form the second resin layer, thereby obtaining a first intermediate laminate containing the first resin layer and the second resin layer; (2) stretching the first intermediate laminate to obtain a second intermediate laminate including the first optically anisotropic layer and the second optically anisotropic layer, the angle between the slow axis of the first optically anisotropic layer and the slow axis of the second optically anisotropic layer being 85° or more and 95° or less; and and (3) laminating the third optically anisotropic layer on the second intermediate laminate. A method for producing an optically anisotropic laminate.

[15] The method for producing an optically anisotropic laminate according to

[14] , wherein the step (3) includes bonding the third optically anisotropic layer to the second intermediate laminate.

[16] The method for producing an optically anisotropic laminate according to

[14] , wherein the step (3) includes applying a coating liquid (C) onto the second intermediate laminate to form the third optically anisotropic layer.

[17] The method for producing an optically anisotropic laminate according to

[16] , wherein the coating liquid (C) contains a liquid crystal compound or a polymer, or a liquid crystal compound and a polymer. Effect of the Invention

[0008] According to the present invention, it is possible to obtain a circular polarizing plate that can suppress coloring due to reflection of external light in both the front direction and the inclined direction of the display surface, and to provide an optically anisotropic laminate having excellent heat resistance; a method for producing the optically anisotropic laminate; a circular polarizing plate including the optically anisotropic laminate; and an image display device including the optically anisotropic laminate. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a cross-sectional view that illustrates an optically anisotropic laminate according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a perspective view showing a schematic view of an evaluation model set when calculating color space coordinates in the simulations of the examples and comparative examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present invention will be described in detail below with reference to embodiments and examples. However, the present invention is not limited to the embodiments and examples shown below, and may be modified and implemented as desired without departing from the scope of the claims of the present invention and the scope of equivalents thereto. The components of the embodiments shown below may be combined as appropriate. In addition, in the drawings, the same components are denoted by the same reference numerals, and their description may be omitted.

[0011] In the following description, the in-plane retardation Re is a value expressed by Re=(nx-ny)×d unless otherwise specified. The thickness direction retardation Rth is a value expressed by Rth={(nx+ny) / 2-nz}×d unless otherwise specified. nx represents the refractive index in the direction perpendicular to the thickness direction (in-plane direction) and giving the maximum refractive index (slow axis direction), ny represents the refractive index in the in-plane direction perpendicular to the direction of nx, nz represents the refractive index in the thickness direction, and d represents the thickness. The measurement wavelength is 550 nm unless otherwise specified. The in-plane retardation and the thickness direction retardation can be measured using a retardation meter (Axometrics' "AxoScan").

[0012] In the following description, the slow axis of a certain layer refers to the slow axis in the in-plane direction of the layer, unless otherwise specified.

[0013] In the following description, the angle between the optical axes (absorption axis, transmission axis, slow axis, etc.) of each layer in a member having multiple layers represents the angle when the layer is viewed from the thickness direction, unless otherwise specified.

[0014] In the following description, unless otherwise specified, the front direction of a certain surface means the normal direction of the surface, and specifically refers to the direction of the polar angle of 0° and the azimuth angle of 0° of the surface.

[0015] In the following description, unless otherwise specified, the tilt direction of a certain face means a direction that is neither parallel nor perpendicular to the face, and specifically refers to a direction in which the polar angle of the face is in the range of greater than 0° and less than 90°.

[0016] In the following description, unless otherwise specified, the directions of elements as "parallel," "vertical," and "orthogonal" may include an error within a range that does not impair the effect of the present invention, for example, within a range of ±5°, ±3°, ±2°, or ±1°.

[0017] In the following description, a "long" film refers to a film having a length of 5 times or more its width, preferably 10 times or more its width, specifically a film having a length that can be wound into a roll for storage or transportation. There is no particular upper limit to the length of a long film, and it can be, for example, 100,000 times or less its width.

[0018] In the following description, the angular relationship between the direction of the optical axis (slow axis, transmission axis, absorption axis, etc.) in the plane of a certain product (optically anisotropic laminate, circular polarizing plate, etc.) and the geometric direction (longitudinal direction, width direction, etc. of the film) is defined as a shift in one direction being positive and a shift in the other direction being negative, unless otherwise specified, and the positive and negative directions are defined commonly for the components in the product. For example, in a certain circular polarizing plate, "the angle made by the slow axis of the λ / 2 layer with respect to the longitudinal direction of the circular polarizing plate is 45°, and the angle made by the slow axis of the λ / 4 layer with respect to the longitudinal direction of the circular polarizing plate is 135°" refers to the following two cases: When the circular polarizer is observed from one side, the slow axis of the λ / 2 layer is shifted 45° clockwise from the longitudinal direction of the circular polarizer, and the slow axis of the λ / 4 layer is shifted 135° clockwise from the longitudinal direction of the circular polarizer. When the circular polarizer is observed from one side, the slow axis of the λ / 2 layer is shifted 45° counterclockwise from the longitudinal direction of the circular polarizer, and the slow axis of the λ / 4 layer is shifted 135° counterclockwise from the longitudinal direction of the circular polarizer.

[0019] In the following description, unless otherwise specified, the oblique direction of a long film refers to an in-plane direction of the film that is neither parallel nor perpendicular to the longitudinal direction of the film.

[0020] In the following description, "a polymer having a positive intrinsic birefringence value" and "a resin having a positive intrinsic birefringence value" mean "a polymer whose refractive index in the stretching direction is greater than that in the direction perpendicular to the stretching direction" and "a resin whose refractive index in the stretching direction is greater than that in the direction perpendicular to the stretching direction", respectively. Also, "a polymer having a negative intrinsic birefringence value" and "a resin having a negative intrinsic birefringence value" mean "a polymer whose refractive index in the stretching direction is smaller than that in the direction perpendicular to the stretching direction" and "a resin whose refractive index in the stretching direction is smaller than that in the direction perpendicular to the stretching direction", respectively. The intrinsic birefringence value can be calculated from the dielectric constant distribution.

[0021] In the following description, unless otherwise specified, the terms "polarizing plate," "circularly polarizing plate," "plate," "λ / 2 plate," and "λ / 4 plate" include not only rigid members but also flexible members such as resin films.

[0022] In the following description, unless otherwise specified, the adhesive refers not only to adhesives in the narrow sense (adhesives having a shear storage modulus of 1 MPa to 500 MPa at 23°C after irradiation with energy rays or after heat treatment) but also to pressure-sensitive adhesives having a shear storage modulus of less than 1 MPa at 23°C.

[0023] [1. Optically anisotropic laminate] [1.1. Overview] The optically anisotropic laminate according to one embodiment of the present invention includes a first optically anisotropic layer, a second optically anisotropic layer, and a third optically anisotropic layer. By combining the optically anisotropic laminate according to this embodiment with a linear polarizer, a circular polarizing plate capable of suppressing coloring due to reflection of external light in both the front direction and the tilt direction of the display surface can be obtained. In addition, the optically anisotropic laminate according to this embodiment has excellent heat resistance.

[0024] The optically anisotropic laminate satisfies the following formulae (1), (2), (3), (4), and (5).

[0025] nx1>ny1≧nz1 (1) nz2≧nx2>ny2 (2) nz3>nx3≧ny3 (3) Re1(450) / Re1(550) <Re2(450) / Re2(550) (4) Re1(550)>Re2(550)>Re3(550) (5)

[0026] however, nx1 represents a refractive index in an in-plane direction of the first optically anisotropic layer that gives the maximum refractive index, ny1 represents a refractive index in an in-plane direction of the first optically anisotropic layer that is perpendicular to the direction that gives nx1, and nz1 represents a refractive index in a thickness direction of the first optically anisotropic layer, nx2 represents a refractive index in an in-plane direction of the second optically anisotropic layer that gives the maximum refractive index, ny2 represents a refractive index in an in-plane direction of the second optically anisotropic layer that is perpendicular to the direction that gives nx2, and nz2 represents a refractive index in a thickness direction of the second optically anisotropic layer, nx3 represents a refractive index in an in-plane direction of the third optically anisotropic layer that gives the maximum refractive index, ny3 represents a refractive index in an in-plane direction of the third optically anisotropic layer that is perpendicular to the direction that gives nx3, and nz3 represents a refractive index in a thickness direction of the third optically anisotropic layer, Re1(450) represents an in-plane retardation of the first optically anisotropic layer at a wavelength of 450 nm, and Re1(550) represents an in-plane retardation of the first optically anisotropic layer at a wavelength of 550 nm, Re2(450) represents an in-plane retardation of the second optically anisotropic layer at a wavelength of 450 nm, and Re2(550) represents an in-plane retardation of the second optically anisotropic layer at a wavelength of 550 nm, Re3(550) represents the in-plane retardation of the third optically anisotropic layer at a wavelength of 550 nm.

[0027] In the optically anisotropic laminate of the present embodiment, the angle between the slow axis of the first optically anisotropic layer and the slow axis of the second optically anisotropic layer is 85° or more and 95° or less.

[0028] The above formula (1) indicates that the first optically anisotropic layer can function as a so-called positive A plate or negative B plate. The above formula (2) indicates that the second optically anisotropic layer can function as a so-called negative A plate or positive B plate.

[0029] The above formula (3) indicates that the third optically anisotropic layer can function as a so-called positive C plate or positive B plate.

[0030] The formula (4) indicates that the wavelength dispersion of the second optically anisotropic layer is greater than that of the first optically anisotropic layer.

[0031] The value of "Re2(450) / Re2(550)-Re1(450) / Re1(550)" is usually greater than 0 and preferably satisfies the following formula (7). Re2(450) / Re2(550)-Re1(450) / Re1(550)≧0.05 (7) The value of "Re2(450) / Re2(550)-Re1(450) / Re1(550)" is preferably 0.05 or more, more preferably 0.07 or more, and even more preferably 0.10 or more. The larger the value, the better, but it may be, for example, 0.8 or less. In this way, an optically anisotropic laminate having a first optically anisotropic layer and a second optically anisotropic layer with different wavelength dispersion of in-plane retardation can easily obtain reverse wavelength dispersion characteristics in a laminated state. Therefore, the optically anisotropic laminate can be combined with a linear polarizer to form a circular polarizing plate that functions in a wide wavelength range.

[0032] The value of "Re2(450) / Re2(550)" is preferably 1.05 or more, more preferably 1.07 or more, and particularly preferably 1.10 or more, and may be, for example, 1.8 or less, although it is not particularly limited. When the value of "Re2(450) / Re2(550)" is within the above range, a circular polarizing plate capable of effectively suppressing coloring due to reflection of external light can be obtained.

[0033] The value of "Re1(450) / Re1(550)" is not particularly limited, but may be, for example, 0.8 or more, and is preferably 1.05 or less, more preferably 1.03 or less, and particularly preferably 1.01 or less. When "Re1(450) / Re1(550)" is within the above range, a circular polarizing plate that can effectively suppress coloring due to reflection of external light can be obtained.

[0034] The value of (Re1(550)-Re2(550)) is usually greater than 0, and is preferably a value that allows the optically anisotropic laminate to function as a λ / 4 plate. Specifically, the optically anisotropic laminate preferably satisfies the following formula (6). 100nm≦(Re1(550)-Re2(550))≦180nm (6) The value of "Re1(550)-Re2(550)" is preferably 100 nm or more, more preferably 110 nm or more, and is preferably 180 nm or less, more preferably 160 nm or less. When "Re1(550)-Re2(550)" is within the above range, a circular polarizing plate that can effectively suppress coloring due to reflection of external light can be obtained.

[0035] The formula (5) indicates that the magnitude of the in-plane retardation at a wavelength of 550 nm is in the order of the first optically anisotropic layer, the second optically anisotropic layer, and the third optically anisotropic layer.

[0036] The value of Re1(550) is preferably 220 nm or more, more preferably 240 nm or more, particularly preferably 250 nm or more, and is preferably 310 nm or less, more preferably 290 nm or less, particularly preferably 280 nm or less, provided that the above formulae (1) to (5) are satisfied. When the in-plane retardation Re1(550) is within the above range, the first optically anisotropic layer can function as a λ / 2 plate. And, according to the optically anisotropic laminate including the first optically anisotropic layer, a circular polarizing plate capable of effectively suppressing coloring due to reflection of external light can be obtained.

[0037] The value of Re2(550) is preferably 80 nm or more, more preferably 100 nm or more, particularly preferably 110 nm or more, and is preferably 170 nm or less, more preferably 150 nm or less, particularly preferably 140 nm or less, provided that the above formulae (1) to (5) are satisfied. When the in-plane retardation Re2(550) is within the above range, the second optically anisotropic layer can function as a λ / 4 plate. And, according to the optically anisotropic laminate including the second optically anisotropic layer, a circular polarizing plate capable of effectively suppressing coloring due to reflection of external light can be obtained.

[0038] The value of Re3(550) is usually 0 nm or more, and may be 0 nm, and is preferably 50 nm or less, more preferably 20 nm or less, and further preferably 5 nm or less, provided that the above formulas (1) to (5) are satisfied.

[0039] The angle between the slow axis of the first optically anisotropic layer and the slow axis of the second optically anisotropic layer is usually 85° or more, preferably 87° or more, more preferably 88° or more, even more preferably 89° or more, and is usually 95° or less, preferably 93° or less, more preferably 92° or less, even more preferably 91° or less, and most preferably 90°. When the angle between the slow axis of the first optically anisotropic layer and the slow axis of the second optically anisotropic layer is within the above range, the heat resistance of the optically anisotropic laminate can be effectively improved.

[0040] In a long optically anisotropic laminate, it is preferable that one of the slow axis of the first optically anisotropic layer and the slow axis of the second optically anisotropic layer forms an angle in a specific range close to 45° with respect to the width direction of the optically anisotropic laminate. Specifically, the angle is preferably 40° or more, more preferably 42° or more, even more preferably 43° or more, particularly preferably 44° or more, and preferably 50° or less, more preferably 48° or less, even more preferably 47° or less, and particularly preferably 46° or less. Furthermore, in this case, it is preferable that the other of the slow axis of the first optically anisotropic layer and the slow axis of the second optically anisotropic layer forms an angle in a specific range close to 135° with respect to the width direction of the optically anisotropic laminate. Specifically, the angle is preferably 130° or more, more preferably 132° or more, even more preferably 133° or more, particularly preferably 134° or more, and preferably 140° or less, more preferably 138° or less, even more preferably 137° or less, and particularly preferably 136° or less. A typical long linear polarizer has an absorption axis parallel or perpendicular to the width direction of the linear polarizer. A long optically anisotropic laminate having a first optically anisotropic layer and a second optically anisotropic layer having a slow axis in a direction that forms an angle within the above range with respect to the width direction can be simply laminated to the typical linear polarizer so that the width direction of the optically anisotropic laminate is parallel to the width direction of the linear polarizer to obtain a circular polarizing plate. Therefore, the lamination of the optically anisotropic laminate and the linear polarizer can be performed by roll-to-roll, so that the circular polarizing plate can be particularly easily manufactured.

[0041] There is no particular limitation on the thickness of each of the first optically anisotropic layer and the second optically anisotropic layer. The thickness of each of the first optically anisotropic layer and the second optically anisotropic layer is preferably 0.5 μm or more, more preferably 1 μm or more, and is preferably 150 μm or less, more preferably 100 μm or less.

[0042] There is no particular limitation on the thickness of the third optically anisotropic layer, but the thickness of the third optically anisotropic layer is preferably 1 μm or more, more preferably 1.2 μm or more, and is preferably 5 μm or less, more preferably 3 μm or less.

[0043] The first optically anisotropic layer, the second optically anisotropic layer, and the third optically anisotropic layer may each have a single layer structure or a multi-layer structure. Here, generally, nx, ny, and nz for the entire layer (referred to as layer (A)) having a multi-layer structure are calculated from the in-plane retardation Re and the retardation Rth in the thickness direction for the entire layer (A) having the multi-layer structure, the thickness of the entire layer (A), and the average refractive index nave of the layer (A). The average refractive index nave can be determined by the following formula. nave = Σ(ni × Li) / ΣLi ni: Refractive index of the resin of layer i in layer (A) Thickness of Li:i layer

[0044] The first optically anisotropic layer, the second optically anisotropic layer, and the third optically anisotropic layer each independently preferably have a single-layer structure.

[0045] [1.2. Materials that form each layer] The first optically anisotropic layer, the second optically anisotropic layer, and the third optically anisotropic layer may be formed from any material. Each of the first optically anisotropic layer, the second optically anisotropic layer, and the third optically anisotropic layer usually contains a resin and is formed from a resin. The resin contained in each of the first optically anisotropic layer, the second optically anisotropic layer, and the third optically anisotropic layer may be a resin having a positive or negative intrinsic birefringence value.

[0046] A resin having a positive intrinsic birefringence value usually contains a polymer having a positive intrinsic birefringence value. Examples of this polymer include polyolefins such as polyethylene and polypropylene; polyesters such as polyethylene terephthalate and polybutylene terephthalate; polyarylene sulfides such as polyphenylene sulfide; polyvinyl alcohol; polycarbonate; polyarylate; cellulose ester; polyether sulfone; polysulfone; polyarylsulfone; polyvinyl chloride; alicyclic structure-containing polymers; rod-shaped liquid crystal polymers; and the like. These polymers may be used alone or in combination of two or more at any ratio. Among them, alicyclic structure-containing polymers, cellulose esters, and polycarbonates are preferred, and alicyclic structure-containing polymers are particularly preferred. The alicyclic structure-containing polymer may be a cyclic olefin-based polymer. The cyclic olefin-based polymer means a polymer having a structural unit obtained by polymerizing a cyclic olefin, or a hydrogenated product thereof. The cyclic olefin may or may not have a substituent.

[0047] The alicyclic structure-containing polymer is a polymer containing an alicyclic structure in the repeating unit, and is usually an amorphous polymer. As the alicyclic structure-containing polymer, both a polymer containing an alicyclic structure in the main chain and a polymer containing an alicyclic structure in the side chain can be used. As the alicyclic structure, for example, a cycloalkane structure and a cycloalkene structure can be mentioned, and from the viewpoint of thermal stability, a cycloalkane structure is preferable. The number of carbon atoms contained in one alicyclic structure is preferably 4 or more, more preferably 5 or more, particularly preferably 6 or more, and preferably 30 or less, more preferably 20 or less, particularly preferably 15 or less.

[0048] In the alicyclic structure-containing polymer, the ratio of the repeating unit containing the alicyclic structure is preferably 50% by weight or more, more preferably 70% by weight or more, and particularly preferably 90% by weight or more. When the ratio of the repeating unit containing the alicyclic structure is within the above range, an optically anisotropic laminate having excellent heat resistance can be obtained.

[0049] Examples of the polymer containing an alicyclic structure include (1) norbornene-based polymers, (2) monocyclic olefin polymers, (3) cyclic conjugated diene polymers, (4) vinyl alicyclic hydrocarbon polymers, and hydrogenated products thereof. Among these, cyclic olefin polymers and norbornene-based polymers are preferred, and norbornene-based polymers are particularly preferred. Examples of the norbornene-based polymers include ring-opening polymers of monomers containing a norbornene structure, ring-opening copolymers of monomers containing a norbornene structure and other monomers copolymerizable therewith, and hydrogenated products thereof; addition polymers of monomers containing a norbornene structure, and addition copolymers of monomers containing a norbornene structure and other monomers copolymerizable therewith. Among these, from the viewpoint of transparency, ring-opening polymer hydrogenated products of monomers containing a norbornene structure are particularly preferred. The above-mentioned alicyclic structure-containing polymers can be selected from the polymers disclosed in, for example, JP-A-2002-321302.

[0050] Examples of cellulose esters include lower fatty acid esters of cellulose (e.g., cellulose acetate, cellulose acetate butyrate, and cellulose acetate propionate). Lower fatty acid refers to fatty acids having 6 or less carbon atoms per molecule. Cellulose acetate can include triacetyl cellulose (TAC) and cellulose diacetate (DAC).

[0051] The total acyl group substitution degree of cellulose ester is preferably 2.20 or more and 2.70 or less, more preferably 2.40 or more and 2.60 or less.Here, the total acyl group can be measured according to ASTM D817-91.In addition, the weight average polymerization degree of cellulose ester is preferably 350 or more and 800 or less, more preferably 370 or more and 600 or less.

[0052] Polycarbonates usually have a repeating unit containing a carbonate bond (-OC(=O)-O-). Examples of polycarbonates include polymers having a structural unit derived from a dihydroxy compound and a carbonate structure (a structure represented by -O-(C=O)-O-). Examples of dihydroxy compounds include bisphenol A. The structural unit derived from a dihydroxy compound contained in a polycarbonate may be one type or two or more types.

[0053] The weight average molecular weight (Mw) of the polymer contained in the resin having a positive intrinsic birefringence value is preferably 10,000 or more, more preferably 15,000 or more, particularly preferably 20,000 or more, and is preferably 100,000 or less, more preferably 80,000 or less, particularly preferably 50,000 or less. When the weight average molecular weight is in such a range, the mechanical strength and moldability of the optically anisotropic layer are highly balanced. The weight average molecular weight is a weight average molecular weight in terms of polyisoprene or polystyrene measured by gel permeation chromatography (GPC) using cyclohexane as a solvent. However, if the sample is not soluble in cyclohexane, toluene may be used as the GPC solvent.

[0054] The molecular weight distribution (weight average molecular weight (Mw) / number average molecular weight (Mn)) of the polymer contained in the resin having a positive intrinsic birefringence value is preferably 1.2 or more, more preferably 1.5 or more, particularly preferably 1.8 or more, and is preferably 3.5 or less, more preferably 3.0 or less, particularly preferably 2.7 or less. When the molecular weight distribution is equal to or more than the lower limit of the above range, the productivity of the polymer can be increased and the production cost can be reduced. When the molecular weight distribution is equal to or less than the upper limit, the amount of low molecular weight components is reduced, thereby suppressing relaxation during exposure to high temperatures and improving the stability of the optically anisotropic layer.

[0055] The proportion of the polymer in the resin having a positive intrinsic birefringence value is preferably 50% by weight to 100% by weight, more preferably 70% by weight to 100% by weight, and particularly preferably 90% by weight to 100% by weight. When the proportion of the polymer is within the above range, the optically anisotropic layer can have sufficient heat resistance and transparency.

[0056] The resin having a positive intrinsic birefringence value may further contain an optional component in combination with the polymer. Examples of the optional component include stabilizers such as antioxidants, heat stabilizers, light stabilizers, weather stabilizers, ultraviolet absorbers, and near infrared absorbers; plasticizers; and the like. These components may be used alone or in combination of two or more at any ratio.

[0057] A resin having a negative intrinsic birefringence value usually contains a polymer having a negative intrinsic birefringence value. Examples of this polymer include polystyrene-based polymers (homopolymers of styrene or styrene derivatives (e.g., 2-vinylnaphthalene) (e.g., polystyrene, poly(2-vinylnaphthalene)), and copolymers of styrene or styrene derivatives with any monomer); polyacrylonitrile polymers; polymethyl methacrylate polymers; or multicomponent copolymers thereof. Examples of any monomers that can be copolymerized with styrene or styrene derivatives include acrylonitrile, maleic anhydride, methyl methacrylate, and butadiene. These polymers may be used alone or in combination of two or more at any ratio.

[0058] Among the polymers having a negative intrinsic birefringence value, polystyrene-based polymers are preferred from the viewpoint of high retardation expression. Among them, copolymers of styrene or styrene derivatives and maleic anhydride are particularly preferred from the viewpoint of high heat resistance. In this copolymer, the amount of maleic anhydride units is preferably 5 parts by weight or more, more preferably 10 parts by weight or more, particularly preferably 15 parts by weight or more, and preferably 30 parts by weight or less, more preferably 28 parts by weight or less, particularly preferably 26 parts by weight or less, based on 100 parts by weight of the polystyrene-based polymer. The maleic anhydride unit refers to a structural unit having a structure formed by polymerizing maleic anhydride.

[0059] The ratio of the polymer in the resin having a negative intrinsic birefringence value is preferably 50% by weight to 100% by weight, more preferably 70% by weight to 100% by weight, and particularly preferably 90% by weight to 100% by weight. When the ratio of the polymer is within the above range, the second optically anisotropic layer can exhibit appropriate optical properties.

[0060] The resin having a negative inherent birefringence value may further contain an optional component in combination with the above-mentioned polymer. The optional component may be, for example, the same as the optional component that may be contained in the resin having a positive inherent birefringence value. The optional component may be used alone or in combination of two or more types in any ratio.

[0061] The first optically anisotropic layer, the second optically anisotropic layer and the third optically anisotropic layer may each comprise a liquid crystal alignment layer. The liquid crystal alignment layer is a cured layer obtained by curing a layer of a liquid crystal composition containing an aligned liquid crystal compound. The liquid crystal alignment layer is formed of a cured liquid crystal composition, and therefore contains molecules of the liquid crystal compound.

[0062] In the liquid crystal alignment layer, the liquid crystal compounds are preferably aligned so as to achieve optical properties required for the liquid crystal alignment layer.

[0063] The liquid crystal compound is preferably polymerizable. Therefore, the liquid crystal compound preferably contains a polymerizable group such as an acryloyl group, a methacryloyl group, and an epoxy group in its molecule. The number of polymerizable groups per molecule of the liquid crystal compound may be one, but is preferably two or more. The liquid crystal compound having polymerizability can be polymerized in a state of exhibiting a liquid crystal phase, and can become a polymer so as not to change the direction showing the maximum refractive index in the refractive index ellipsoid of the molecules in the liquid crystal phase. Therefore, when the liquid crystal compound has polymerizability, it is possible to fix the alignment state of the liquid crystal compound in the liquid crystal alignment layer, or to increase the degree of polymerization of the liquid crystal compound to increase the mechanical strength of the liquid crystal alignment layer.

[0064] The liquid crystal compound may be used alone or in combination of two or more kinds in any ratio.

[0065] The liquid crystal composition may further contain an optional component in combination with the liquid crystal compound, if necessary. The optional component may be used alone or in combination of two or more at any ratio. Examples of the optional component include polymerization initiators, surfactants, antioxidants, metals, metal complexes, metal oxides such as titanium oxide, colorants such as dyes and pigments, light-emitting materials such as fluorescent materials and phosphorescent materials, leveling agents, thixotropic agents, gelling agents, polysaccharides, ultraviolet absorbers, infrared absorbers, antioxidants, ion exchange resins, etc. The amount of each of these components may be 0.1 to 20 parts by weight relative to 100 parts by weight of the total of the liquid crystal compounds.

[0066] Examples of liquid crystal compositions that can form a liquid crystal alignment layer include the liquid crystal composition described in JP-A-2002-333642, a composition containing a liquid crystal compound having a polymerizable group, a composition containing a side-chain liquid crystal polymer, and a composition containing a discotic liquid crystal compound. Examples of liquid crystal compounds having a polymerizable group include rod-shaped liquid crystal compounds having a polymerizable group described in JP-A-11-513360, JP-A-2002-030042, JP-A-2004-204190, JP-A-2005-263789, JP-A-2007-119415, and JP-A-2007-186430. Examples of side-chain liquid crystal polymer compounds include side-chain liquid crystal polymer compounds described in JP-A-2002-333642 and JP-A-2003-177242. As a preferred example of the liquid crystal compound, there may be mentioned, by product name, "LC242" manufactured by BASF.

[0067] The hardening of a liquid crystal composition is usually achieved by polymerization of a polymerizable compound contained in the liquid crystal composition. Thus, the liquid crystal alignment layer usually contains a polymer of some or all of the components contained in the liquid crystal composition. Thus, when the liquid crystal compound is polymerizable, the liquid crystal alignment layer can be a layer containing a polymer of the liquid crystal compound. Generally, the liquid crystallinity of a liquid crystal compound is lost by polymerization, but in the present application, such polymerized liquid crystal compounds are also included in the term "liquid crystal compound contained in the liquid crystal alignment layer."

[0068] In the liquid crystal alignment layer, the fluidity of the liquid crystal composition is lost. Therefore, the alignment state of the liquid crystal compound can usually be fixed in the liquid crystal alignment layer. The term "liquid crystal compound having a fixed alignment state" includes a polymer of the liquid crystal compound. The liquid crystal alignment layer may contain molecules of a liquid crystal compound having an unfixed alignment state in combination with the molecules of the liquid crystal compound having a fixed alignment state, but it is preferable that all of the molecules of the liquid crystal compound contained in the liquid crystal alignment layer have a fixed alignment state.

[0069] The method for forming the liquid crystal alignment layer is not particularly limited, but for example, the liquid crystal alignment layer can be formed by carrying out the steps of forming a layer of a liquid crystal composition containing a liquid crystal compound on a base film, orienting the liquid crystal compound contained in the layer of liquid crystal composition, and curing the layer of liquid crystal composition.

[0070] [1.3. Preferred form of the first optically anisotropic layer] The first optically anisotropic layer preferably contains a resin (A) having a positive intrinsic birefringence value and is formed from the resin (A). Examples and preferred examples of the resin (A) having a positive intrinsic birefringence value include the examples and preferred examples given above as the resin having a positive intrinsic birefringence value. The first optically anisotropic layer is preferably a layer (first stretched layer) obtained by stretching a first resin layer containing a resin (A) having a positive intrinsic birefringence value, whereby the first optically anisotropic layer satisfying the above formula (1) can be easily formed.

[0071] In another embodiment, the first optically anisotropic layer preferably includes a liquid crystal alignment layer. Examples of the liquid crystal alignment layer that can be included in the first optically anisotropic layer include the examples of the liquid crystal alignment layer described above.

[0072] In the liquid crystal alignment layer that can be included in the first optically anisotropic layer, the liquid crystal compound is preferably homogeneously aligned, which makes it easy to realize the first optically anisotropic layer that satisfies formula (1).

[0073] [1.4. Preferred form of the second optically anisotropic layer] The second optically anisotropic layer preferably contains a resin having an intrinsic birefringence value with a sign opposite to that of the resin contained in the first optically anisotropic layer, more preferably contains a resin (B) having a negative intrinsic birefringence value, and more preferably is formed from a resin (B). Examples and preferred examples of the resin (B) having a negative intrinsic birefringence value include the examples and preferred examples given above as the resin having a negative intrinsic birefringence value. The second optically anisotropic layer is preferably a layer (second stretched layer) obtained by stretching a second resin layer containing a resin (B) having a negative intrinsic birefringence value, whereby the second optically anisotropic layer satisfying the above formula (2) can be easily formed.

[0074] In another embodiment, the second optically anisotropic layer preferably comprises a liquid crystal alignment layer. Examples of the liquid crystal alignment layer that can be included in the second optically anisotropic layer include the examples of the liquid crystal alignment layer described above.

[0075] In the liquid crystal alignment layer that can be included in the second optically anisotropic layer, the liquid crystal compound is preferably homogeneously aligned, which makes it easy to realize the second optically anisotropic layer that satisfies formula (2).

[0076] [1.5. Preferred form of the third optically anisotropic layer] The third optically anisotropic layer preferably includes a liquid crystal alignment layer. Examples of the liquid crystal alignment layer that can be included in the third optically anisotropic layer include the above-mentioned examples of the liquid crystal alignment layer.

[0077] In the liquid crystal alignment layer that can be included in the third optically anisotropic layer, the liquid crystal compound is preferably in a homeotropic alignment, which makes it easy to realize a second optically anisotropic layer that satisfies formula (3).

[0078] In another embodiment, the third optically anisotropic layer preferably contains a resin (C) having a negative intrinsic birefringence value and is formed from the resin (C). Examples and preferred examples of the resin (C) having a negative intrinsic birefringence value include the examples and preferred examples given above as the resin having a negative intrinsic birefringence value. In another embodiment, the third optically anisotropic layer is preferably a layer (third stretched layer) obtained by stretching a third resin layer containing a resin (C) having a negative intrinsic birefringence value, thereby making it possible to easily form the third optically anisotropic layer satisfying the above formula (3).

[0079] [1.6. Configuration of optically anisotropic laminate] The first optically anisotropic layer, the second optically anisotropic layer, and the third optically anisotropic layer included in the optically anisotropic laminate may be arranged in any order. That is, the optically anisotropic laminate may have the following configurations (1) to (3). (1) The optically anisotropic laminate comprises the first optically anisotropic layer, the second optically anisotropic layer, and the third optically anisotropic layer in this order. (2) The optically anisotropic laminate comprises the first optically anisotropic layer, the third optically anisotropic layer, and the second optically anisotropic layer in this order. (3) The optically anisotropic laminate comprises the third optically anisotropic layer, the first optically anisotropic layer, and the second optically anisotropic layer in this order.

[0080] Preferably, the optically anisotropic laminate has the above-mentioned configuration (1) or (3). The optically anisotropic laminate having the above-mentioned configuration (1) or (3) can be easily produced by laminating a third optically anisotropic layer on an intermediate laminate in which the first optically anisotropic layer and the second optically anisotropic layer are laminated.

[0081] An example of an optically anisotropic laminate will be described with reference to the drawings. FIG. 1 is a cross-sectional view showing a schematic diagram of an optically anisotropic laminate according to one embodiment of the present invention. As shown in FIG. 1, an optically anisotropic laminate 100 includes a first optically anisotropic layer 110, a second optically anisotropic layer 120, and the third optically anisotropic layer 130 in this order. The first optically anisotropic layer 110 and the second optically anisotropic layer 120 are directly connected to each other without any layer therebetween. The second optically anisotropic layer 120 and the third optically anisotropic layer 130 are directly connected to each other without any layer therebetween.

[0082] The optically anisotropic laminate may have any layer other than the first optically anisotropic layer, the second optically anisotropic layer, and the third optically anisotropic layer, as necessary. Examples of the optional layer include any layer having optical isotropy. The optional layer having optical isotropy usually has an in-plane retardation of 10 nm or less at a wavelength of 550 nm, and examples thereof include a protective film layer for protecting the first optically anisotropic layer, the second optically anisotropic layer, and the third optically anisotropic layer; an adhesive layer for bonding each layer such as the first optically anisotropic layer, the second optically anisotropic layer, and the third optically anisotropic layer; and the like. Another example of the optional layer includes any layer having optical anisotropy.

[0083] The optically anisotropic laminate may be a sheet of film or a long film.

[0084] The optically anisotropic laminate preferably has a retardation that can function as a λ / 4 plate. The optically anisotropic laminate has an in-plane retardation at a wavelength of 550 nm of preferably 75 nm or more, more preferably 100 nm or more, and preferably 180 nm or less, more preferably 160 nm or less. When the in-plane retardation of the optically anisotropic laminate is within the above range, a circular polarizing plate that can effectively suppress coloring due to reflection of external light can be obtained.

[0085] The optically anisotropic laminate preferably exhibits reverse wavelength dispersion. When the optically anisotropic laminate has reverse wavelength dispersion, a circular polarizing plate that functions in a wide wavelength range can be obtained from the optically anisotropic laminate. The optically anisotropic laminate preferably satisfies the following formula. Re(450) / Re(550) <Re(650) / Re(550) Here, Re(450) represents the in-plane retardation of the optically anisotropic laminate at a wavelength of 450 nm, Re(550) represents the in-plane retardation of the optically anisotropic laminate at a wavelength of 550 nm, and Re(650) represents the in-plane retardation of the optically anisotropic laminate at a wavelength of 650 nm.

[0086] The value of Re(450) / Re(550) is preferably 0.75 or more, more preferably 0.80 or more, and is preferably 0.95 or less, more preferably 0.92 or less. The value of Re(650) / Re(550) is preferably 1.02 or more, more preferably 1.03 or more, and is preferably 1.25 or less, more preferably 1.20 or less.

[0087] The total light transmittance of the optically anisotropic laminate is preferably 80% or more, more preferably 85% or more, and particularly preferably 90% or more. The total light transmittance can be measured in the wavelength range of 400 nm to 700 nm using an ultraviolet-visible spectrometer.

[0088] The haze of the optically anisotropic laminate is preferably 5% or less, more preferably 3% or less, particularly preferably 1% or less, and ideally 0%. The haze can be measured using a haze meter in accordance with JIS K7361-1997.

[0089] The thickness of the optically anisotropic laminate is not particularly limited. From the viewpoint of thinning, the specific thickness of the optically anisotropic laminate is preferably 5 μm or more, more preferably 10 μm or more, particularly preferably 15 μm or more, and is preferably 200 μm or less, more preferably 150 μm or less, particularly preferably 100 μm or less.

[0090] [1.7. Heat resistance of optically anisotropic laminate] The optically anisotropic laminate has high heat resistance. Specifically, the optically anisotropic laminate has a small retardation change due to heat. The in-plane retardation of the optically anisotropic laminate at a wavelength of 550 nm before a heat resistance test in which the optically anisotropic laminate is heated at 85° C. for 500 hours is defined as Reb(550), and the in-plane retardation of the optically anisotropic laminate at a wavelength of 550 nm after the heat resistance test is defined as Rea(550). The absolute value |Reb(550)-Rea(550)| is preferably 10 nm or less, more preferably 5 nm or less, and even more preferably 3 nm or less. The closer to 0 nm the better, but it may be 0.5 nm or more.

[0091] The reason why the optically anisotropic laminate according to this embodiment has high heat resistance is presumed to be the following, although this is not intended to limit the present invention. The optically anisotropic laminate includes a first optically anisotropic layer having an in-plane retardation and a second optically anisotropic layer having an in-plane retardation. When a resin film having an in-plane retardation is heated, the in-plane retardation tends to become smaller. This phenomenon is believed to occur because the orientation of polymer molecules contained in the resin is relaxed by heating. When the optically anisotropic laminate is heated, the in-plane retardation of each of the first optically anisotropic layer and the second optically anisotropic layer is also believed to become smaller than that before heating. The angle between the slow axis of the first optically anisotropic layer and the slow axis of the second optically anisotropic layer is close to or equal to 90°. In this case, the in-plane retardation of the laminate including the first optically anisotropic layer and the second optically anisotropic layer is usually the difference between the in-plane retardation of the first optically anisotropic layer and the in-plane retardation of the second optically anisotropic layer. Here, when the laminate including the first optically anisotropic layer and the second optically anisotropic layer is heated, both the in-plane retardation of the first optically anisotropic layer and the in-plane retardation of the second optically anisotropic layer tend to be smaller than before heating. Therefore, even if the optically anisotropic laminate including the first optically anisotropic layer and the second optically anisotropic layer is heated, the in-plane retardation of the optically anisotropic laminate fluctuates less than that of an optically anisotropic member that is not a laminate. For these reasons, it is believed that the optically anisotropic laminate according to this embodiment has high heat resistance.

[0092] [2. Manufacturing method of optically anisotropic laminate] The optically anisotropic laminate can be produced by any method. For example, the first optically anisotropic layer, the second optically anisotropic layer, and the third optically anisotropic layer are prepared and laminated together to produce the optically anisotropic laminate. For lamination, a suitable adhesive or a layer of a suitable adhesive may be used.

[0093] The order in which the first optically anisotropic layer, the second optically anisotropic layer, and the third optically anisotropic layer are laminated may be arbitrary. An optically anisotropic laminate may be produced by producing a laminate including any two layers of the first optically anisotropic layer, the second optically anisotropic layer, and the third optically anisotropic layer, and laminating the remaining layer on the laminate.

[0094] The first optically anisotropic layer, the second optically anisotropic layer, and the third optically anisotropic layer may each be produced by any method. Alternatively, any one of the first optically anisotropic layer, the second optically anisotropic layer, and the third optically anisotropic layer may be formed on a substrate film, and then laminated to another layer, and the substrate film may be removed to form the layers.

[0095] Alternatively, the optically anisotropic laminate may be manufactured by a manufacturing method including a step (1) of preparing a first intermediate laminate including a first resin layer including the resin (A) and a second resin layer including the resin (B), a step (2) of stretching the first intermediate laminate to obtain a second intermediate laminate, and a step (3) of laminating a third optically anisotropic layer on the second intermediate laminate. Here, the steps (1), (2), and (3) are usually performed in this order. In addition, the first intermediate laminate and the second intermediate laminate may each be a sheet, but are preferably long. By preparing the first intermediate laminate and the second intermediate laminate as long bodies, the optically anisotropic laminate can be manufactured simply and efficiently.

[0096] The first intermediate laminate can be manufactured by any method. For example, the first intermediate laminate can be manufactured by a co-extrusion method, a co-casting method, a coating method in which a liquid composition containing a material of a layer is applied onto a certain layer, and the like. Among them, a method in which a liquid composition (coating liquid (B)) containing a resin (B) is applied onto the first resin layer, and the applied liquid composition is dried as necessary, is preferred.

[0097] The step (1) preferably includes the step (1a). In step (1a), a coating liquid (B) containing a resin (B) is applied onto the first resin layer to form a second resin layer, thereby obtaining a first intermediate laminate containing the first resin layer and the second resin layer.

[0098] Here, the first resin layer contains the resin (A) as described above and is formed from the resin (A). The first resin layer can be produced by any method. The first resin layer can be produced, for example, by a melt molding method or a solution casting method. Among these, the melt molding method is preferred. Among the melt molding methods, the extrusion molding method, the inflation molding method or the press molding method is preferred, and the extrusion molding method is particularly preferred. According to these methods, the first resin layer can be produced as a long film.

[0099] The coating liquid (B) may contain a solvent in addition to the resin (B). The solvent is preferably one capable of dissolving or dispersing the resin (B), and particularly preferably one capable of dissolving the resin (B). The solvent may be used alone or in combination of two or more types at any ratio. The concentration of the resin (B) in the coating liquid (B) is preferably adjusted so that the viscosity of the coating liquid (B) falls within a range suitable for coating, and may be, for example, 1% by weight to 50% by weight.

[0100] There is no limitation on the method for applying the coating liquid (B). Examples of the application method include curtain coating, extrusion coating, roll coating, spin coating, dip coating, bar coating, spray coating, slide coating, print coating, gravure coating, die coating, and gap coating.

[0101] By applying the coating liquid (B) containing the resin (B), a layer of the coating liquid (B) is formed on the first resin layer. Therefore, if necessary, the layer of the coating liquid (B) is dried to remove the solvent, and a second resin layer is formed on the first resin layer, thereby obtaining a first intermediate laminate. There is no limitation on the drying method, and for example, drying methods such as heat drying and reduced pressure drying can be used.

[0102] In step (2), the first intermediate laminate is stretched to obtain a second intermediate laminate. The slow axes of the first optically anisotropic layer and the second optically anisotropic layer included in the second intermediate laminate form a predetermined angle. Since the first resin layer contains a resin (A) having a positive intrinsic birefringence value and the second resin layer contains a resin (B) having a negative intrinsic birefringence value, by stretching the first intermediate laminate including the first resin layer and the second resin layer, the first resin layer usually has a slow axis in the same direction as the stretching direction, preferably the same direction, and the second resin layer usually has a slow axis in the direction of approximately 90°, preferably 90°, to the stretching direction.

[0103] Therefore, in the second intermediate laminate, the angle between the slow axis of the first optically anisotropic layer and the slow axis of the second optically anisotropic layer is preferably 85° or more, more preferably 87° or more, even more preferably 88° or more, even more preferably 89° or more, and is preferably 95° or less, more preferably 93° or less, even more preferably 92° or less, even more preferably 91° or less, and most preferably 90°.

[0104] The stretching of the first intermediate laminate in step (2) can be carried out in any direction, and the stretching may be carried out in one step or in two or more steps.

[0105] Preferably, when the long first intermediate laminate is stretched in step (2), the stretching direction of the first intermediate laminate in step (2) is preferably at an angle of a specific range close to 45° with respect to the width direction of the first intermediate laminate. Specifically, the angle is preferably 40° or more, more preferably 42° or more, even more preferably 43° or more, particularly preferably 44° or more, and is preferably 50° or less, more preferably 48° or less, even more preferably 47° or less, particularly preferably 46° or less. When stretching is performed at the above stretching angle, the slow axis of the optically anisotropic laminate can usually be at an angle close to 45° with respect to the width direction of the optically anisotropic laminate, so that the optically anisotropic laminate can be laminated to a long linear polarizer by roll-to-roll to produce a circular polarizing plate in a particularly simple manner.

[0106] The stretching ratio of the first intermediate laminate in step (2) is preferably greater than 1.0, more preferably 1.05 or more, even more preferably 1.1 or more, even more preferably 1.2 or more, even more preferably 1.3 or more, and particularly preferably 1.35 or more, and is preferably 3.0 or less, more preferably 2.5 or less, and even more preferably 2.0 or less.

[0107] In step (3), the method of laminating the third optically anisotropic layer on the second intermediate laminate is arbitrary. For example, the third optically anisotropic layer may be prepared and laminated on the second intermediate laminate. Thus, in one embodiment, step (3) includes laminating the third optically anisotropic layer on the second intermediate laminate. The third optically anisotropic layer may be produced by any method.

[0108] For example, a third resin layer containing a resin (C) having a negative intrinsic birefringence value is produced, and the third resin layer is stretched to produce a third optically anisotropic layer. The third resin layer can be produced by any method. Examples and preferred examples of the method for producing the third resin layer are the same as the examples and preferred examples of the method for producing the first resin layer.

[0109] In yet another embodiment, step (3) includes applying a coating liquid (C) onto the second intermediate laminate and, if necessary, drying the applied coating liquid (C) to form a third optically anisotropic layer.

[0110] When the third optically anisotropic layer includes a liquid crystal alignment layer, the coating liquid (C) may be a liquid crystal composition including a liquid crystal compound. For example, the liquid crystal composition exemplified in the section on the liquid crystal alignment layer may be used as the liquid crystal composition. The liquid crystal composition may include any component, such as a solvent and a polymerization initiator, in addition to the liquid crystal compound. The total weight of the components in the liquid crystal composition excluding the solvent is preferably adjusted so that the viscosity of the coating liquid (C) falls within a range suitable for coating, and may be, for example, 1% by weight to 50% by weight.

[0111] The coating liquid (C) may contain a polymer. The polymer may be a liquid crystal compound or may not be a liquid crystal compound. An example of the polymer that can be contained in the coating liquid (C) is a side-chain type liquid crystal polymer.

[0112] The method of applying the coating liquid (C) onto the second intermediate laminate is arbitrary. Examples of the application method include the same examples as those given as the application method for the coating liquid (B). When drying the applied coating liquid (C), the drying method is arbitrary, and examples of the method of drying the layer of the coating liquid (B) are given.

[0113] In addition to the above steps (1) to (3), the method for producing the optically anisotropic laminate may include any production method. For example, when a long optically anisotropic laminate is obtained using a long first intermediate laminate or a long second intermediate laminate, the manufacturing method of the optically anisotropic laminate may include a trimming step of cutting the obtained optically anisotropic laminate into a desired shape. The trimming step allows a sheet of an optically anisotropic laminate having a desired shape to be obtained. In addition, the manufacturing method of the optically anisotropic laminate may include, for example, a step of providing a protective layer on the optically anisotropic laminate.

[0114] [3. Circular polarizing plate] A circular polarizing plate according to one embodiment of the present invention includes a linear polarizer and an optically anisotropic laminate. By providing this circular polarizing plate on the display surface of an image display device, reflection of external light can be suppressed. The circular polarizing plate including the optically anisotropic laminate described above can suppress reflection of external light and effectively suppress coloring in both cases where the display surface is viewed from the front direction and the display surface is viewed from an inclined direction.

[0115] The circular polarizing plate preferably comprises a linear polarizer, a first optically anisotropic layer, and a second optically anisotropic layer in this order.

[0116] In addition, the angle between the absorption axis of the linear polarizer or the transmission axis of the linear polarizer and the slow axis of the first optically anisotropic layer is preferably in a specific range close to 45°. Specifically, the angle is preferably 40° or more, more preferably 42° or more, even more preferably 43° or more, particularly preferably 44° or more, and is preferably 50° or less, more preferably 48° or less, even more preferably 47° or less, particularly preferably 46° or less. Furthermore, in this case, the angle between the absorption axis of the linear polarizer or the transmission axis of the linear polarizer and the slow axis of the second optically anisotropic layer is preferably in a specific range close to 135°. Specifically, the angle is preferably 130° or more, more preferably 132° or more, even more preferably 133° or more, particularly preferably 134° or more, and is preferably 140° or less, more preferably 138° or less, even more preferably 137° or less, particularly preferably 136° or less.

[0117] Any linear polarizer can be used as the linear polarizer. Examples of linear polarizers include a film obtained by adsorbing iodine or a dichroic dye to a polyvinyl alcohol film, and then uniaxially stretching the film in a boric acid bath; a film obtained by adsorbing iodine or a dichroic dye to a polyvinyl alcohol film, stretching the film, and further modifying a part of the polyvinyl alcohol unit in the molecular chain to a polyvinylene unit; and a film obtained by the above. Among these, the linear polarizer is preferably a polarizer containing polyvinyl alcohol.

[0118] When natural light is incident on a linear polarizer, only one polarized light is transmitted. The degree of polarization of this linear polarizer is not particularly limited, but is preferably 98% or more, and more preferably 99% or more. The thickness of the linear polarizer is preferably 5 μm to 80 μm.

[0119] The circularly polarizing plate described above may further include an optional layer. Examples of the optional layer include a polarizer protective film layer, an adhesive layer for bonding a linear polarizer and an optically anisotropic laminate, a hard coat layer such as an impact-resistant polymethacrylate resin layer, a matte layer for improving the slipperiness of the film, a reflection suppressing layer, an antifouling layer, an antistatic layer, and the like. Only one of these optional layers may be provided, or two or more layers may be provided.

[0120] [4. Image display devices] The circular polarizing plate described above can be provided in an image display device. In particular, it is preferable that the circular polarizing plate is provided in an organic electroluminescence image display device. This organic electroluminescence image display device includes a circular polarizing plate and an organic electroluminescence element (hereinafter, sometimes referred to as an "organic EL element" as appropriate). This organic electroluminescence image display device usually includes a linear polarizer, an optically anisotropic laminate, and an organic EL element in this order.

[0121] The organic EL element includes a transparent electrode layer, a light-emitting layer, and an electrode layer in this order, and the light-emitting layer can emit light by applying a voltage from the transparent electrode layer and the electrode layer. Examples of materials constituting the organic light-emitting layer include polyparaphenylenevinylene-based, polyfluorene-based, and polyvinylcarbazole-based materials. The light-emitting layer may also have a laminate of layers with different luminescent colors, or a mixed layer in which a dye layer is doped with a different dye. Furthermore, the organic EL element may have functional layers such as a hole injection layer, a hole transport layer, an electron injection layer, an electron transport layer, an equipotential surface forming layer, and a charge generation layer.

[0122] The image display device can suppress reflection of external light on the display surface. Specifically, only a part of the linearly polarized light incident from outside the device passes through a linear polarizer, and then passes through an optically anisotropic laminate to become circularly polarized light. The circularly polarized light is reflected by a component that reflects light in the image display device (such as a reflective electrode in an organic EL element), and passes through the optically anisotropic laminate again to become linearly polarized light having a vibration direction perpendicular to the vibration direction of the incident linearly polarized light, and does not pass through the linear polarizer. Here, the vibration direction of the linearly polarized light means the vibration direction of the electric field of the linearly polarized light. This achieves the function of suppressing reflection.

[0123] Since the optically anisotropic laminate has the above-mentioned optical properties, the organic EL image display device can exhibit the reflection suppressing function not only in the front direction of the display surface but also in the inclined direction, thereby making it possible to effectively suppress the reflection of external light and suppress coloring in both the front direction and the inclined direction of the display surface.

[0124] The degree of coloring is the color difference ΔE between the chromaticity measured by observing a reflective display surface and the chromaticity of a non-reflective black display surface. * The chromaticity can be evaluated by measuring the spectrum of light reflected from the display surface, multiplying the spectrum by the spectral sensitivity (color matching function) corresponding to the human eye to obtain tristimulus values ​​X, Y, and Z, and calculating the chromaticity (a * ,b * ,L * ) can be obtained by calculating the color difference ΔE * ab is the chromaticity when the display surface is not illuminated by external light (a0 * ,b0 * ,L0 * ), and chromaticity when illuminated by external light (a1 * ,b1 * ,L1 * ) can be calculated from the following formula (X).

[0125]

number

[0126] In general, the coloring of the display surface due to reflected light can vary depending on the azimuth angle of the observation direction. Therefore, when observing from an inclined direction of the display surface, the measured chromaticity can vary depending on the azimuth angle of the observation direction, so the color difference ΔE * Therefore, in order to evaluate the degree of coloring when observed from an inclined direction of the display surface as described above, the color difference ΔE obtained by observing from multiple azimuth angle directions can be calculated. * It is preferable to perform color evaluation according to the average value of ab. Specifically, in the azimuth angle range of 0° to less than 360° (see FIG. 2) at 5° intervals in the azimuth angle direction, the color difference ΔE * Measure ab and measure the color difference ΔE * The degree of coloring is evaluated based on the average value of ab (average color difference). The smaller the average color difference, the less coloring there is on the display surface when observed from an inclined direction. EXAMPLES

[0127] The present invention will be described in detail below with reference to examples. However, the present invention is not limited to the examples shown below, and can be modified and carried out as desired without departing from the scope of the claims of the present invention and the scope of equivalents thereto.

[0128] In the following description, the units "%" and "parts" are by weight unless otherwise specified. Furthermore, the operations described below were carried out at room temperature (20°C ± 15°C) and normal pressure (1 atm) unless otherwise specified.

[0129] [Evaluation method] (Thickness) The thickness of the laminate and each layer was measured using a film thickness measurement system ("F20" manufactured by Filmetrics).

[0130] (Method of measuring phase difference) Using a retardation meter (Axometrics' "AxoScan"), the in-plane retardation Re of the evaluation target film at wavelengths of 450 nm, 550 nm, and 650 nm and at a temperature of 23° C., and the thickness direction retardation Rth at a wavelength of 550 nm and at a temperature of 23° C. were measured. Similarly, measurements using the retardation meter were also performed at a temperature of 23° C. When determining the physical properties of each layer of an inseparable laminate, the sample was measured from multiple directions and the properties were calculated by fitting analysis using the attached multilayer analysis software.

[0131] (Method of measuring orientation angle) The direction of the slow axis of each layer constituting the optically anisotropic laminate was measured using a retardation meter (AxoScan manufactured by Axometrics). The angle that this slow axis made with respect to the width direction of each layer was calculated as the orientation angle θ (0°≦θ<180°).

[0132] (Retardation fluctuation due to heat resistance test) A sample was cut out from the optically anisotropic laminate into a 50 mm x 50 mm square. The sample was cut out so that each side was parallel to the width direction or length direction of the long optically anisotropic laminate. The phase difference of the cut out optically anisotropic laminate sample was measured using a phase difference meter (Axometrics' "AxoScan"). The sample was then left to stand in a thermostatic chamber at 85°C for 500 hours, and then removed from the thermostatic chamber to measure the phase difference. The heat resistance was evaluated by determining the difference in phase difference before and after the heat resistance test.

[0133] (ΔE * ab: Simulation method for calculating color difference) The circularly polarizing plates manufactured in each of the Examples and Comparative Examples were modeled using "LCD Master" manufactured by Shintech Co., Ltd. as simulation software, and the following calculations were performed.

[0134] In the simulation model, a circular polarizing plate was provided on the reflection surface of a mirror having a flat reflection surface. The arrangement of the optically anisotropic laminate and the linear polarizer in the circular polarizing plate was set to be the same as in each Example and Comparative Example, and the order was set to be the reflection surface, the linear polarizer, and the optically anisotropic laminate. The optically anisotropic laminate obtained in each Example and Comparative Example was set. In addition, a commonly used polarizing plate with a polarization degree of 99.99% was set as the linear polarizer. In addition, an ideal mirror that can mirror-reflect incident light with a reflectance of 100% was set as the mirror.

[0135] FIG. 2 is a perspective view showing a schematic view of an evaluation model set when calculating color space coordinates in the simulations of the examples and comparative examples. As shown in FIG. 2, the color space coordinates observed on the reflective surface 10 of the mirror provided with a circular polarizer when illuminated by a D65 light source (not shown) were calculated. Also, the color space coordinates when not illuminated by the light source were a0 * =0,b0 * =0,L0 * = 0. Then, from (i) the color space coordinates when illuminated by the light source and (ii) the color space coordinates when not illuminated by the light source, the color difference ΔE * I asked for ab.

[0136] The color difference ΔE * The calculation of ab is performed in the observation direction 20 where the polar angle ρ with respect to the reflecting surface 10 is 0°, and the color difference ΔE * The polar angle ρ represents the angle formed with respect to the normal direction 11 of the reflecting surface 10.

[0137] In addition, the color difference ΔE * The calculation of ab was performed in an observation direction 20 with a polar angle ρ of 60° relative to the reflecting surface 10. This calculation at polar angle ρ = 60° was performed multiple times by moving the observation direction 20 in the azimuth angle direction, with the azimuth angle φ moving in 5° increments within a range of 0° or more and less than 360°. The azimuth angle φ represents the angle that a direction parallel to the reflecting surface 10 makes with a certain reference direction 12 that is parallel to the reflecting surface 10. The color difference ΔE in the multiple calculated observation directions 20 was *Calculate the average of ab and calculate the color difference ΔE in the tilt direction of polar angle ρ = 60°. * I got ab.

[0138] (Method of visually evaluating circularly polarizing plates in the front direction) An image display device (Apple's "AppleWatch" (registered trademark)) equipped with an organic EL image display device was prepared. This image display device was disassembled, and the polarizing plate attached to the surface of the organic EL image display device was peeled off to expose the reflective electrode. The surface of this reflective electrode was attached to the surface of the circular polarizing plate obtained in each Example and Comparative Example opposite to the linear polarizer via an adhesive ("CS9621" manufactured by Nitto Denko Corporation). This resulted in a sample equipped with the reflective electrode, adhesive, and circular polarizing plate in this order.

[0139] The circular polarizer sample was illuminated with sunlight on a sunny day, and the circular polarizer on the reflective electrode was visually observed. The observation was performed in the front direction of the circular polarizer with a polar angle of 0° and an azimuth angle of 0°. If a chromatic color was visible as a result of the observation, it was judged as "poor", and if a chromatic color was not visible, it was judged as "good".

[0140] (Method of visually evaluating circularly polarizing plates in the tilt direction) The circular polarizer sample prepared in the above (method of visually evaluating a circular polarizer in the front direction) was illuminated with sunlight on a sunny day, and the circular polarizer on the reflective electrode was visually observed. The observation was performed at a polar angle of 60° and an azimuth angle of 0° to 360°. As a result of the observation, the reflection luminance and coloring were comprehensively judged to be superior or inferior, and the Examples and Comparative Examples were ranked. The ranked Examples and Comparative Examples were then given points corresponding to their rank (1st place: 7 points, 2nd place: 6 points, ....lowest: 1 point).

[0141] The above observations were performed by a large number of people, and the total score of the given points was calculated for each Example and Comparative Example. The Examples and Comparative Examples were ranked in order of the above total score, and the range of the total score was divided into 5 equal parts, and the top group was ranked in the order of A, B, C, D, and E.

[0142] (Heat resistance: Visual evaluation method for circularly polarizing plates before and after heat resistance test) The circular polarizer (1) or circular polarizer (2) obtained in each Example and Comparative Example was attached to an organic EL image display device in the same manner as described above (method of visually evaluating a circular polarizer in the front direction). The circular polarizer on the reflective electrode was visually observed while the sample circular polarizer was illuminated with sunlight on a sunny day. The observation was performed in the front direction of the circular polarizer with a polar angle of 0° and an azimuth angle of 0°. As a result of the observation, if there was a change in hue between the image display device attached with the circular polarizer (1) and the image display device attached with the circular polarizer (2), it was judged as "poor", and if there was no change in hue, it was judged as "good".

[0143] [Example 1] (1-1. Formation of the first resin layer) Pellet-shaped norbornene-based resin (ZEONOR 1215 manufactured by ZEON CORPORATION; glass transition temperature 126°C) was dried at 100°C for 5 hours to obtain a thermoplastic resin (A). This thermoplastic resin (A) was fed to an extruder, passed through a polymer pipe and a polymer filter, and extruded from a T-die into a sheet shape onto a casting drum. The extruded thermoplastic resin (A) was cooled to obtain a long resin film with a thickness of 100 µm as a first resin layer. The obtained first resin layer was wound into a roll and collected.

[0144] (1-2. Formation of second resin layer) In a dried, nitrogen-purged pressure reactor, 500 ml of toluene as a solvent and 0.29 mmol of n-butyl lithium as a polymerization catalyst were added, and then 35 g of 2-vinylnaphthalene was added and reacted at 25°C for 1 hour. As a result, a reaction product containing poly(2-vinylnaphthalene) as a homopolymer of 2-vinylnaphthalene was obtained. This reaction product was poured into a large amount of 2-propanol to precipitate poly(2-vinylnaphthalene), which was then separated. The obtained poly(2-vinylnaphthalene) was dried at 200°C for 24 hours using a vacuum dryer to obtain a thermoplastic resin (B). The weight-average molecular weight of poly(2-vinylnaphthalene) measured by GPC was 250,000. The glass transition temperature of poly(2-vinylnaphthalene) measured by a differential scanning calorimeter was 142°C.

[0145] Poly(2-vinylnaphthalene) and 1,3-dioxolane were mixed to obtain a liquid composition containing a thermoplastic resin (B) as a coating liquid (B). The concentration of poly(2-vinylnaphthalene) in this liquid composition was 15% by weight.

[0146] The first resin layer was pulled out from the roll, and the liquid composition was applied onto the pulled out first resin layer. The applied liquid composition was then dried to form a layer (thickness 12 μm) of poly(2-vinylnaphthalene) as a second resin layer on the first resin layer. This resulted in a first intermediate laminate having a first resin layer formed of a norbornene-based resin and a second resin layer formed of poly(2-vinylnaphthalene). The obtained first intermediate laminate was wound into a roll and collected.

[0147] (1-3. Process (2): Stretching process) The first intermediate laminate was pulled out from the roll, and the pulled out first intermediate laminate was fed to a tenter-type stretching machine. Using this tenter-type stretching machine, the first intermediate laminate was stretched in a stretching direction at an angle of 45° to the width direction of the first intermediate laminate at a stretching temperature of 135°C and a stretching ratio of 2.0 times to obtain a long second intermediate laminate. This second intermediate laminate had a first stretched layer as the first optically anisotropic layer obtained by stretching the first resin layer, and a second stretched layer as the second optically anisotropic layer obtained by stretching the second resin layer.

[0148] From the stretching direction in the stretching process and the respective orientation angles of the first optically anisotropic layer and the second optically anisotropic layer, it was confirmed that the norbornene-based resin forming the first optically anisotropic layer has a positive intrinsic birefringence value, and the poly(2-vinylnaphthalene) forming the second optically anisotropic layer has a negative intrinsic birefringence value.

[0149] (1-4. Preparation of third optically anisotropic layer) A side-chain liquid crystal polymer represented by the following chemical formula (I) (weight average molecular weight Mw: 5000, Patent Document 2: compound described in JP-A-2014-026266) was prepared.

[0150] [ka]

[0151] A liquid crystal composition was prepared as coating liquid (C) by dissolving 20 parts by weight of the side-chain liquid crystal polymer, 80 parts by weight of "Paliocolor LC242" manufactured by BASF as a liquid crystal compound having a polymerizable group and exhibiting a nematic liquid crystal phase, and 5 parts by weight of "Irgacure 907" manufactured by Ciba Specialty Chemicals as a photopolymerization initiator in 200 parts by weight of cyclopentanone as a solvent.

[0152] The liquid crystal composition was applied to a substrate film, Zeonex Film (norbornene-based resin film) manufactured by Zeon Corporation, using a bar coater to form a layer of the liquid crystal composition on the substrate film. The layer of the liquid crystal composition was dried by heating at 80°C for 4 minutes. This caused the liquid crystal compounds in the liquid crystal composition to be aligned. The dried layer of the liquid crystal composition was irradiated with ultraviolet light to harden the layer of the liquid crystal composition, forming a liquid crystal alignment layer having a thickness of 0.58 µm as a third optically anisotropic layer on the substrate film.

[0153] (1-5. Process (3): Lamination process) The second intermediate laminate obtained by stretching in the stretching step was pulled out from the roll, and the second optically anisotropic layer of the pulled out second intermediate laminate was faced to the third optically anisotropic layer (liquid crystal alignment layer) on the base film and laminated together via an acrylic adhesive ("CS9621" manufactured by Nitto Denko Corporation). The lamination was performed so that the width direction of the long second intermediate laminate was parallel to the width direction of the long third optically anisotropic layer.

[0154] Next, the substrate film was removed, and the third optically anisotropic layer was transferred to the second intermediate laminate to obtain an optically anisotropic laminate having the first optically anisotropic layer, the second optically anisotropic layer, and the third optically anisotropic layer in this order. The optical properties (in-plane retardation, thickness direction retardation, direction of slow axis) of the obtained optically anisotropic laminate and each layer contained in the optically anisotropic laminate were measured by the above-mentioned method. In addition, a sample was cut out to 50 mm x 50 mm square from the optically anisotropic laminate, and the difference in in-plane retardation before and after the heat resistance test was obtained by the above-mentioned method. The difference in in-plane retardation was less than 1 nm.

[0155] (1-6. Manufacturing of circularly polarizing plates) A long polyvinyl alcohol resin film dyed with iodine was prepared. This film was stretched in a longitudinal direction at an angle of 90° to the width direction of the film to obtain a linear polarizer as a long polarizing film. This linear polarizer had an absorption axis in the longitudinal direction of the linear polarizer and a transmission axis in the width direction of the linear polarizer.

[0156] The linear polarizer and the optically anisotropic laminate were bonded together so that the linear polarizer and the first optically anisotropic layer faced each other via an optically isotropic pressure-sensitive adhesive ("CS9621" manufactured by Nitto Denko Corporation) to obtain a circular polarizing plate (1). The bonding was performed so that the width direction of the linear polarizer was parallel to the width direction of the long optically anisotropic laminate. The obtained circular polarizing plate (1) had a linear polarizer, a first optically anisotropic layer, a second optically anisotropic layer, and a third optically anisotropic layer in this order. The obtained circular polarizing plate (1) was evaluated by the method described above. In addition, in the same manner as the circular polarizing plate (1), the optically anisotropic laminate sample after the heat resistance test was attached to the linear polarizer to obtain a circular polarizing plate (2).

[0157] [Example 2] In Example 1 (1-5. Step (3): Lamination step), the first optically anisotropic layer of the second intermediate laminate and the third optically anisotropic layer on the substrate film were laminated facing each other via an acrylic adhesive. Except for the above, the same operation as in Example 1 was performed to obtain an optically anisotropic laminate. In addition, a sample of 50 mm x 50 mm square was cut out from the optically anisotropic laminate, and the difference in in-plane retardation before and after the heat resistance test was determined by the above-mentioned method. The difference in in-plane retardation was less than 1 nm.

[0158] Next, the linear polarizer and the optically anisotropic laminate were bonded together so that the linear polarizer and the third optically anisotropic layer faced each other via an optically isotropic adhesive ("CS9621" manufactured by Nitto Denko Corporation). Except for the above, the same operation as in (1-6. Manufacture of circularly polarizing plate) of Example 1 was performed to obtain a circularly polarizing plate (1). The obtained circularly polarizing plate (1) had a linear polarizer, a third optically anisotropic layer, a first optically anisotropic layer, and a second optically anisotropic layer in this order. The obtained circularly polarizing plate (1) was evaluated. In addition, in the same manner as the circularly polarizing plate (1), the optically anisotropic laminate sample after the heat resistance test was bonded to the linear polarizer to obtain a circularly polarizing plate (2).

[0159] [Example 3] A first intermediate laminate was obtained by the same operation as in Example 1. The first intermediate laminate was fed to a free uniaxial stretching machine and free uniaxially stretched at a stretching temperature of 135°C, in a stretching direction at an angle of 90° to the width direction of the first intermediate laminate, and at a stretch ratio of 1.7 times, to obtain a second intermediate laminate.

[0160] Using the obtained second intermediate laminate, an optically anisotropic laminate was obtained by the same operation as in Example 1. In addition, a sample of 50 mm x 50 mm square was cut out from the optically anisotropic laminate, and the difference in in-plane retardation before and after the heat resistance test was obtained by the above-mentioned method. The difference in in-plane retardation was less than 1 nm.

[0161] Next, a rectangular sheet of optically anisotropic laminate was cut out from the long optically anisotropic laminate. The cutting was performed so that each side of the sheet of optically anisotropic laminate was parallel to the longitudinal direction or width direction of the long optically anisotropic laminate. The cut optically anisotropic laminate and a linear polarizer obtained by the same operation as in Example 1 were laminated opposite each other via an acrylic adhesive ("CS9621" manufactured by Nitto Denko Corporation) to obtain a circular polarizing plate (1). The lamination was performed so that the slow axis of the first optically anisotropic layer of the optically anisotropic laminate and the transmission axis direction of the linear polarizer form an angle of 45°. The obtained circular polarizing plate (1) was provided with a linear polarizer, a first optically anisotropic layer, a second optically anisotropic layer, and a third optically anisotropic layer in this order. The obtained circular polarizing plate (1) was evaluated by the above-mentioned method. In the same manner as for the circular polarizing plate (1), the optically anisotropic laminate sample after the heat resistance test was attached to the linear polarizer to obtain a circular polarizing plate (2).

[0162] [Comparative Example 1] In (1-6. Production of circularly polarizing plate) of Example 1, circularly polarizing plate (1) and circularly polarizing plate (2) were obtained by using the second intermediate laminate obtained in Example 1 instead of the optically anisotropic laminate. The obtained circularly polarizing plate (1) and circularly polarizing plate (2) had a linear polarizer, a first optically anisotropic layer, and a second optically anisotropic layer in this order. The obtained circularly polarizing plate (1) was evaluated by the method described above. In addition, the optical properties of the second intermediate laminate and each layer included in the second intermediate laminate were measured by the method described above.

[0163] [Comparative Example 2] (C2-1. Production of First Optically Anisotropic Layer) A rolled unstretched film having a thickness of 70 μm and made of norbornene resin (ZEON Corporation's "ZEONOR 1215"; glass transition temperature 126° C.) was fed to a tenter-type stretching machine and obliquely stretched at 133° C. to obtain a stretched film having a thickness of 45 μm as a first optically anisotropic layer. The oblique stretching was performed continuously by making the feed speeds of the left and right sides of the stretching machine different. The optical properties of the obtained first optically anisotropic layer were measured by the above-mentioned method. The slow axis of the obtained first optically anisotropic layer was in a direction of 67.5° with respect to the width direction.

[0164] (C2-2. Production of second optically anisotropic layer) A rolled unstretched film having a thickness of 50 μm and formed from a norbornene resin (ZEON Corporation's "ZEONOR 1215"; glass transition temperature 126° C.) was fed to a tenter-type stretching machine and uniaxially stretched transversely at 128° C. to obtain a stretched film having a thickness of 40 μm as a second optically anisotropic layer. The stretching was performed continuously at a magnification of 1.526 times. The optical properties of the obtained second optically anisotropic layer were measured by the method described above. The slow axis of the obtained second optically anisotropic layer was parallel (0°) to the width direction.

[0165] (C2-3. Production of optically anisotropic laminate) The first optically anisotropic layer and the second optically anisotropic layer were laminated together with an acrylic adhesive ("CS9621" manufactured by Nitto Denko Corporation) in such a manner that they faced each other to obtain an intermediate laminate. The lamination was performed so that the width direction of the long first optically anisotropic layer was parallel to the width direction of the long second optically anisotropic layer.

[0166] A third optically anisotropic layer was formed on a substrate film in the same manner as in (1-4. Preparation of third optically anisotropic layer) of Example 1, except for the following changes. The thickness of the liquid crystal alignment layer was adjusted by adjusting the coating thickness using a bar coater so that Rth(550) was the desired value. The second optically anisotropic layer of the intermediate laminate and the third optically anisotropic layer on the base film were laminated together, facing each other via an acrylic adhesive ("CS9621" manufactured by Nitto Denko Corporation). The lamination was performed so that the width direction of the long intermediate laminate was parallel to the width direction of the long third optically anisotropic layer.

[0167] Next, the substrate film was removed, and the third optically anisotropic layer was transferred to the intermediate laminate to obtain an optically anisotropic laminate having the first optically anisotropic layer, the second optically anisotropic layer, and the third optically anisotropic layer in this order. The optical properties (in-plane retardation, thickness direction retardation, direction of slow axis) of the obtained optically anisotropic laminate and each layer contained in the optically anisotropic laminate were measured by the above-mentioned method. In addition, a sample was cut out to 50 mm x 50 mm square from the optically anisotropic laminate, and the difference in in-plane retardation before and after the heat resistance test was obtained by the above-mentioned method. The difference in in-plane retardation was 1 nm.

[0168] (C2-4. Manufacturing of circularly polarizing plates) Using the obtained optically anisotropic laminate, circular polarizing plates (1) and (2) were obtained in the same manner as in (1-6. Production of circular polarizing plate) of Example 1. The obtained circular polarizing plate (1) was evaluated by the method described above.

[0169] [Comparative Example 3] A first optically anisotropic layer was obtained in the same manner as in Comparative Example 2 (C2-1. Production of first optically anisotropic layer).

[0170] A third optically anisotropic layer was formed on a substrate film in the same manner as in Example 1 (1-4. Preparation of third optically anisotropic layer), except for the following changes. The thickness of the liquid crystal alignment layer was adjusted by adjusting the coating thickness using a bar coater so that Rth(550) was the desired value.

[0171] The first optically anisotropic layer and the third optically anisotropic layer on the base film were laminated together facing each other via an acrylic adhesive ("CS9621" manufactured by Nitto Denko Corporation). The lamination was performed so that the width direction of the long first optically anisotropic layer was parallel to the width direction of the long third optically anisotropic layer.

[0172] Next, the base film was removed, and the third optically anisotropic layer was transferred to the first optically anisotropic layer to obtain an intermediate laminate including the first optically anisotropic layer and the third optically anisotropic layer.

[0173] A second optically anisotropic layer was obtained in the same manner as in Comparative Example 2 (C2-2. Production of second optically anisotropic layer).

[0174] The third optically anisotropic layer of the intermediate laminate and the second optically anisotropic layer were laminated together by facing each other through an acrylic adhesive ("CS9621" manufactured by Nitto Denko Corporation). The lamination was performed so that the width direction of the long intermediate laminate and the width direction of the long second optically anisotropic layer were parallel. This resulted in an optically anisotropic laminate having the first optically anisotropic layer, the third optically anisotropic layer, and the second optically anisotropic layer in this order.

[0175] The optical properties (in-plane retardation, thickness retardation, slow axis direction) of the obtained optically anisotropic laminate and each layer contained in the optically anisotropic laminate were measured by the above-mentioned method. In addition, a sample of 50 mm x 50 mm square was cut out from the optically anisotropic laminate, and the difference in in-plane retardation before and after the heat resistance test was obtained by the above-mentioned method. The difference in in-plane retardation was 1 nm.

[0176] Using the obtained optically anisotropic laminate, circular polarizing plates (1) and (2) were obtained in the same manner as in (1-6. Production of circular polarizing plate) of Example 1. The obtained circular polarizing plate (1) was evaluated by the method described above.

[0177] [Comparative Example 4] 37.5 parts by weight of isosorbide, 91.5 parts by weight of 9,9-[4-(2-hydroxyethoxy)phenyl]fluorene, 8.4 parts by weight of polyethylene glycol (average molecular weight 400), 105.7 parts by weight of diphenyl carbonate, and 0.594 parts by weight of a 0.2 wt % aqueous solution of cesium carbonate as a catalyst were charged into a reaction vessel and heated and stirred at 150°C for approximately 15 minutes under a nitrogen atmosphere to dissolve the raw materials.

[0178] Next, the pressure in the reaction vessel was set to 13.3 kPa, and the temperature was raised to 190°C in 1 hour while the generated phenol was discharged outside the reaction vessel. Next, the temperature inside the reaction vessel was set to 190°C and maintained for 15 minutes. Next, the pressure in the reaction vessel was set to 6.67 kPa, and the temperature was raised to 230°C in 15 minutes, and the generated phenol was discharged outside the reaction vessel. Next, the temperature was raised to 250°C in 8 minutes, and the pressure in the reaction vessel was reduced to 0.200 kPa or less, and the generated phenol was further discharged outside the reaction vessel.

[0179] After the reaction was completed, the resulting reaction product (polycarbonate resin) was extruded into water and molded into pellets. The resulting polycarbonate resin had a glass transition temperature of 126°C, a reduced viscosity of 0.372 dL / g, and contained 42.9 mol% of structural units derived from 9,9-[4-(2-hydroxyethoxy)phenyl]fluorene, 52.8 mol% of structural units derived from isosorbide, and 4.3 mol% of structural units derived from polyethylene glycol.

[0180] The obtained polycarbonate resin pellets were vacuum dried for 5 hours at 80° C. Next, the polycarbonate resin pellets were fed to a film forming device equipped with a single screw extruder (set temperature: 220° C.), a T-die (set temperature: 220° C.), a cooling drum (set temperature: 120 to 130° C.), and a winder to produce a polycarbonate resin film having a length of 3 m, a width of 300 mm, and a thickness of 120 μm.

[0181] The obtained polycarbonate resin film was stretched in the machine direction at a temperature of 136° C. and a stretching ratio of 2 to obtain a stretched film.

[0182] A third optically anisotropic layer was formed on a substrate film in the same manner as in Example 1 (1-4. Preparation of third optically anisotropic layer), except for the following changes. The thickness of the liquid crystal alignment layer was adjusted by adjusting the coating thickness using a bar coater so that Rth(550) was the desired value.

[0183] The stretched film and the third optically anisotropic layer on the base film were laminated together by facing each other via an acrylic adhesive ("CS9621" manufactured by Nitto Denko Corporation). The lamination was performed so that the width direction of the long stretched film and the width direction of the long third optically anisotropic layer were parallel to each other. This resulted in an optically anisotropic laminate comprising a stretched polycarbonate resin film and a third optically anisotropic layer.

[0184] The optical properties (in-plane retardation, thickness retardation, slow axis direction) of the obtained optically anisotropic laminate and each layer contained in the optically anisotropic laminate were measured by the above-mentioned method. In addition, a sample of 50 mm x 50 mm square was cut out from the optically anisotropic laminate, and the difference in in-plane retardation before and after the heat resistance test was obtained by the above-mentioned method. The difference in in-plane retardation was 4 nm.

[0185] A rectangular sheet of optically anisotropic laminate was cut out from the long optically anisotropic laminate. The cut out sheet of optically anisotropic laminate was cut out so that each side of the sheet of optically anisotropic laminate was parallel to the longitudinal direction or width direction of the long optically anisotropic laminate. The cut out optically anisotropic laminate and a linear polarizer obtained by the same operation as in Example 1 were laminated opposite each other via an acrylic adhesive ("CS9621" manufactured by Nitto Denko Corporation) to obtain a circular polarizing plate (1). The lamination was performed so that the slow axis of the stretched film included in the optically anisotropic laminate and the transmission axis direction of the linear polarizer form an angle of 45°.

[0186] The obtained circular polarizing plate (1) was evaluated by the method described above. In addition, in the same manner as the circular polarizing plate (1), the optically anisotropic laminate sample after the heat resistance test was attached to the linear polarizer to obtain a circular polarizing plate (2).

[0187] [result] The results are shown in the table below. In the table below, the symbols P, A, B, and C in the layer structure represent a linear polarizer, an A layer, a B layer, and a C layer, respectively. For example, "P / A / B / C" indicates that the linear polarizer, the A layer, the B layer, and the C layer are arranged in this order. The "first layer", "second layer", and "third layer" represent the first optically anisotropic layer, the second optically anisotropic layer, and the third optically anisotropic layer, respectively. The "orientation angle" refers to the angle between the width direction of each layer and the slow axis of each layer, where the orientation angle of layer A and the orientation angle of layer B in Example 3 are the angle between the slow angle of layer A and the transmission axis direction of the linear polarizer and the angle between the slow axis of layer B and the transmission axis direction of the linear polarizer, respectively, and the orientation angle of layer A in Comparative Example 4 is the angle between the slow axis of layer A and the transmission axis direction of the linear polarizer. "COP" means norbornene-based resin. "VN" means poly(2-vinylnaphthalene). "LC" means a cured liquid crystal composition. "PC" stands for polycarbonate resin.

[0188] [Table 1]

[0189] [Table 2]

[0190] The above results show that the optically anisotropic laminates of Examples 1 to 3 have good heat resistance, and that the circular polarizing plates obtained from the optically anisotropic laminates can suppress discoloration of the display surface of an image display device in both the front direction and the inclined direction. [Explanation of symbols]

[0191] 10 reflective surface 11 Normal direction of reflecting surface 12 Reference direction 20 Observation direction φ Azimuth ρ polar angle 100 Optically anisotropic laminate 110 First optically anisotropic layer 120 Second optically anisotropic layer 130 Third optically anisotropic layer

Claims

1. An optically anisotropic laminate comprising a first optically anisotropic layer, a second optically anisotropic layer, and a third optically anisotropic layer, the laminate satisfying the following formulas (1), (2), (3), (4), and (5), the angle between a slow axis of the first optically anisotropic layer and a slow axis of the second optically anisotropic layer is 85° or more and 95° or less, and Re1(550) is 220 nm or more. nx1>ny1≧nz1 (1) nz2≧nx2>ny2 (2) nz3>nx3≧ny3 (3) Re1(450) / Re1(550)<Re2(450) / Re2(550) (4) Re1 (550) > Re2 (550) > Re3 (550) (5) however, nx1 represents a refractive index in an in-plane direction of the first optically anisotropic layer that gives the maximum refractive index, ny1 represents a refractive index in an in-plane direction of the first optically anisotropic layer that is perpendicular to the direction that gives nx1, and nz1 represents a refractive index in a thickness direction of the first optically anisotropic layer, nx2 represents a refractive index in an in-plane direction of the second optically anisotropic layer that gives the maximum refractive index, ny2 represents a refractive index in an in-plane direction of the second optically anisotropic layer that is perpendicular to the direction that gives nx2, and nz2 represents a refractive index in a thickness direction of the second optically anisotropic layer, nx3 represents a refractive index in an in-plane direction of the third optically anisotropic layer that gives the maximum refractive index, ny3 represents a refractive index in an in-plane direction of the third optically anisotropic layer that is perpendicular to the direction that gives nx3, and nz3 represents a refractive index in a thickness direction of the third optically anisotropic layer, Re1(450) represents an in-plane retardation of the first optically anisotropic layer at a wavelength of 450 nm, and Re1(550) represents an in-plane retardation of the first optically anisotropic layer at a wavelength of 550 nm; Re2(450) represents an in-plane retardation of the second optically anisotropic layer at a wavelength of 450 nm, and Re2(550) represents an in-plane retardation of the second optically anisotropic layer at a wavelength of 550 nm; Re3(550) represents the in-plane retardation of the third optically anisotropic layer at a wavelength of 550 nm.

2. The optically anisotropic laminate according to claim 1 , further satisfying the following formula (6): 100nm≦(Re1(550)-Re2(550))≦180nm (6) Here, Re1(550) and Re2(550) are each as defined above.

3. The optically anisotropic laminate according to claim 1 , further satisfying the following formula (7): Re2(450) / Re2(550)-Re1(450) / Re1(550)≧0.05 (7) Here, Re1(450), Re1(550), Re2(450), and Re2(550) are each as defined above.

4. the first optically anisotropic layer is a first stretched layer obtained by stretching a first resin layer, The optically anisotropic laminate according to claim 1 , wherein the first resin layer contains a resin (A) having a positive intrinsic birefringence value.

5. The optically anisotropic laminate according to claim 1 , wherein the first optically anisotropic layer comprises a liquid crystal alignment layer.

6. the second optically anisotropic layer is a second stretched layer obtained by stretching a second resin layer, The optically anisotropic laminate according to claim 1 , wherein the second resin layer contains a resin (B) having a negative intrinsic birefringence value.

7. The optically anisotropic laminate according to claim 1 , wherein the second optically anisotropic layer comprises a liquid crystal alignment layer.

8. The optically anisotropic laminate according to claim 1 , wherein the third optically anisotropic layer comprises a liquid crystal alignment layer.

9. the third optically anisotropic layer is a third stretched layer obtained by stretching a third resin layer, The optically anisotropic laminate according to claim 1 , wherein the third resin layer contains a resin (C) having a negative intrinsic birefringence value.

10. the first optically anisotropic layer, the second optically anisotropic layer, and the third optically anisotropic layer in this order; or the first optically anisotropic layer, the third optically anisotropic layer, and the second optically anisotropic layer in this order, or The optically anisotropic laminate according to claim 1 , comprising the third optically anisotropic layer, the first optically anisotropic layer, and the second optically anisotropic layer in this order.

11. The optically anisotropic laminate according to claim 1 , wherein the first optically anisotropic layer comprises an alicyclic structure-containing polymer.

12. A linear polarizer; A circularly polarizing plate comprising the optically anisotropic laminate according to any one of claims 1 to 11.

13. 13. The circularly polarizing plate according to claim 12, wherein an angle between an absorption axis of the linear polarizer or a transmission axis of the linear polarizer and a slow axis of the first optically anisotropic layer is 40° or more and 50° or less.

14. An image display device comprising the circular polarizer according to claim 12 and an organic electroluminescence element, An image display device comprising the linear polarizer, the optically anisotropic laminate, and the organic electroluminescence element in this order.

15. A method for producing an optically anisotropic laminate, comprising the steps of: The optically anisotropic laminate is the optically anisotropic laminate according to claim 4 , wherein the second optically anisotropic layer is a second stretched layer obtained by stretching a second resin layer, and the second resin layer contains a resin (B) having a negative intrinsic birefringence value; The manufacturing method comprises: (1a) forming the second resin layer by applying a coating liquid (B) containing the resin (B) on the first resin layer to obtain a first intermediate laminate containing the first resin layer and the second resin layer; (2) stretching the first intermediate laminate to obtain a second intermediate laminate including the first optically anisotropic layer and the second optically anisotropic layer, the angle between the slow axis of the first optically anisotropic layer and the slow axis of the second optically anisotropic layer being 85° or more and 95° or less; and and (3) laminating the third optically anisotropic layer on the second intermediate laminate. A method for producing an optically anisotropic laminate.

16. The method for producing an optically anisotropic laminate according to claim 15 , wherein the step (3) comprises laminating the third optically anisotropic layer to the second intermediate laminate.

17. The method for producing an optically anisotropic laminate according to claim 15 , wherein the step (3) comprises applying a coating liquid (C) onto the second intermediate laminate to form the third optically anisotropic layer.

18. The method for producing an optically anisotropic laminate according to claim 17 , wherein the coating liquid (C) contains a liquid crystal compound or a polymer, or a liquid crystal compound and a polymer.

Citation Information

Patent Citations

  • Polarizing plate, and liquid crystal display using the same

    JP2005208356A

  • Retardation Film to Eliminate Light Leakage in Crossed Polarizers in LCDs

    JP2008509425A

  • Multilayer optical film, and liquid crystal panel and liquid crystal display device using multilayer optical film

    JP2009251442A

  • Optical film, and method for producing optical film

    JP2019152714A

  • Elliptical polarizer and organic light-emitting device

    JP2021516792A